Comparative study of nasal bacterial carriage in pediatric patients from two different geographical regions - Ghebremedhin, Beniam; Koenig, W. (European journal of microbiology & immunology, 2012)
The aim of this study was to determine the prevalence of bacterial carriage in the anterior nares of two different patient cohorts, aged 5-15 years. By use of a sensitive enrichment broth, Gram-positive and -negative bacteria were cultured from the two cohorts of each 100 patients at the Referral Clinic in Eritrea and at a German University Hospital. In the German cohort, 27% of the patients were positive either for Gram-negative (n=5) or -positive bacteria, including Staphylococcus aureus (n=8; MRSA (n=2)), Staphylococcus epidermidis (n=12), Corynebacterium spp. (n=4), and Streptococcus pyogenes (n=1). In comparison, the Eritrean cohort revealed 33% bacterial carriers in the anterior nares. Among the identified species were S. aureus (n=2), S. epidermidis (n=13), Streptococcus haemolyticus (n=9), and Gram-negative rods including Klebsiella pneumoniae/oxytoca (n=5), Enterobacter agglomerans (n=4), Escherichia coli (n=2), and Pseudomonas aeruginosa (n=1). Noteworthy, none of the Eritrean patients were positive for MRSA. In both cohorts there was no co-occurrence of Gram-positive and -negative bacteria in the anterior nares. However, we observed in two subjects of the Eritrean cohort co-colonization with S. epidermidis and S. haemolyticus. The occurrence of Gram-negative bacteria was less significant by age in the German cohort, whereas in the Eritrean cohort Gram-negative bacteria were more frequently detected in carriers aged 5-9 years. Continued surveillance of S. aureus and Gram-negative bacteria carriage deserves further attention and might help to determine future trends in the characteristics of nasal carriage, subsequent incidence of infections, and the potential effectiveness of targeted population based intervention.